Pituitary in the Spotlight - Reincke, Martin; Honegger, Jürgen (Experimental and Clinical Endocrinology & Diabetes, 2021)
The German Society of Endocrinology (DGE) has a long-standing scientific and clinical focus on the pituitary. The pituitary working group ‘Arbeitsgemeinschaft Hypophyse’ is an interdisciplinary special interest group with a focus on advancing diagnosis and treatment of pituitary conditions. On the occasion of the English publication of the S2K clinical guideline Diagnosis and therapy of clinically hormonally inactive pituitary tumors, we present here a series of 12 articles from internationally renowned authors from inside and outside of Germany.
Keywords: pituitary; adenoma; tumor; neuroendocrine; carcinoma; classification